NEOGENE VERTEBRATES FROM URUMACO, FALCON STATE, VENEZUELA: DIVERSITY AND SIGNIFICANCE - Sanchez-Villagra M.R.; Aguilera O.A. (My University, 2006)
The first palaeontological discoveries in Urumaco were made more than half a century ago. Several research groups have worked in the region, but new vertebrate fossils are still being found in this area of northwestern Venezuela. The most conspicuous elements of the fauna are reptiles, because of their size and abundance, although fishes are by far the most diverse group. Among South American Neogene assemblages the whole fauna is most similar to those of Acre in Brazil and Entre Rios in Argentina. The crocodile fauna includes at least 12 species representing diverse ecomorphological types; most of them lived sympatrically, a unique case in worldwide crocodylomorph assemblages. At least four turtle species provide unique palaeobiogeographical or palaeobiological information. Several freshwater species, including Serrasalminae fish, thorny catfishes, silver croaker, redtail catfishes, matamata turtle, river dolphin and probable sirenians, are consistent with the hypothesis that a tributary and/or delta of the Orinoco existed in this area of north-western Venezuela during late Miocene times.
Keywords: MIOCENE; CROCODILE; TURTLE; FISH; ORINOCO; CARIBBEAN; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен